THE USAGE OF BLENDED LEARNING METHODS TO IMPROVE COMMUNICATIVE SKILLS FOR TEACHING ENGLISH AS A SECOND LANGUAGE (ESL) TO CADETS - Shakhnoza Murakayeva; Lazokat Ikanova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. Blended learning, an educational approach combining traditional face-to-face instruction with online learning, has been widely recognized for its effectiveness in language acquisition, especially in ESL (English as a Second Language) programs. This study explores the role of blended learning methods in enhancing the communicative skills of cadets in ESL education. By integrating digital resources with interactive classroom practices, blended learning not only boosts engagement but also fosters critical language competencies. This paper presents an overview of the blended learning approach, its impact on communicative skills development, and its specific advantages in the structured, regimented environment of military education.